Pelaksanaan Pembinaan Kolaboratif Bagi Guru Untuk Meningkatkan Kualitas Penyusunan Perencanaan Pembelajaran Di SD Negeri 050767 Perkebunan Serapun Tahun Pembelajaran 2018/2019 - Hasnah Hasnah (Universitas Islam Sumatera Utara, 2021)
This study aims to improve the willingness and ability of teachers to develop syllabuses and learning implementation plans (RPP) so that the teaching and learning process is directed and learning achievement increases. Based on the results of syllabus observations in the first cycle, data on the increase in the percentage of suitability was obtained, namely in the component of determining teaching materials from 50% to 75%, learning activities increased from 25% to 75%, indicators from 25% to 75%, types of assessment from 50% to 75%. Meanwhile, in the second cycle, namely the preparation of rpp, there was an increase in terms of determining the learning model, which has increased, namely from 25% increased to 75% and the assessment aspect from 25% increased to 75%, indicators increased from 25% to 75%, learning objectives increased from 50% to 75%, teaching materials from 25% to 75%. Based on the results of the data analysis above, it was concluded that Collaborative coaching can improve teachers' ability to develop syllabuses and lesson implementation plans.